Aluminum lithium adsorbent and preparation method and application thereof

By using a mixed solution of composite lithium source and composite aluminum source, an aluminum-based lithium adsorbent with high lithium adsorption capacity is prepared, which solves the problems of complex processes and low lithium adsorption capacity in the prior art, and achieves the needs of industrial applications.

CN119857460APending Publication Date: 2025-04-22CHENGDU MEIFUTE MEMBRANE TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411730680.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The preparation process of existing aluminum-based lithium adsorbents is complex, and the lithium adsorption capacity is low, making it difficult to meet the needs of industrial applications.

Method used

A mixed solution of composite lithium source and composite aluminum source is used to prepare an aluminum-based lithium adsorption agent with high lithium adsorption capacity by controlling the pH value and reaction conditions.

Benefits of technology

The process has been simplified and the lithium adsorption capacity has been improved. The lithium adsorption capacity can reach 14.4 mg/g, and the stable performance has been maintained during multiple cycles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an aluminum lithium adsorbent as well as a preparation method and application thereof. The preparation method of the aluminum lithium adsorbent comprises the following steps: mixing a composite lithium source solution and a composite aluminum source solution to form a mixed solution; wherein the composite lithium source comprises a first mixture composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate and lithium fluoride; the composite aluminum source comprises a second mixture composed of an acidic aluminum source and an alkaline aluminum source, the acidic aluminum source comprises aluminum chloride and aluminum sulfate, and the alkaline aluminum source comprises sodium metaaluminate; dropwise adding alkali liquor into the mixed liquor until the pH value of the mixed liquor is 4.8-6.5 to obtain a solid-liquid mixture; wherein the alkali liquor comprises an aqueous solution of lithium hydroxide; and collecting and drying the precipitate to obtain the aluminum lithium adsorbent. The preparation method of the aluminum lithium adsorbent is simple in process, and the prepared aluminum lithium adsorbent is high in lithium adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium extraction by adsorption, and in particular to an aluminum-based lithium adsorbent and a preparation method and application thereof. Background Art

[0002] Lithium is an important strategic resource in my country. The development of related industries such as energy storage, 3C consumer electronics, and new energy vehicles continues to drive the demand for lithium resources. There are three main forms of lithium resources: salt lake brine lithium mines in closed basins, pegmatite-type hard rock lithium mines, and sedimentary rock-type clay lithium mines. Among them, salt lake brine lithium mines account for 62.6% of the world's total lithium resources and are the most common form of lithium resources. Although lithium extraction from salt lakes has the advantage of relatively low cost, its technology is developed relatively late and is far less mature than the technology for extracting lithium from ores. Therefore, the current development and utilization of lithium resources in my country is still relatively low.

[0003] Due to the inferior quality of my country's salt lakes and the huge differences between the conditions of various salt lakes, if we want to vigorously develop lithium extraction from salt lakes, we must make up for the shortcomings through technological innovation. Separating lithium ions from sodium ions and magnesium ions in salt lake brine is the key to lithium extraction technology from salt lakes. Because they have similar ion hydration radius or ion radius, it is difficult to separate them, and there is a relatively high technical threshold.

[0004] The adsorption method is one of the most widely used and most practical processes in the current extraction of lithium from salt lakes. The adsorption method mainly relies on adsorbents with specific adsorption capacity for lithium ions to achieve the separation of lithium ions, and then uses eluents to elute lithium ions to form lithium ion solutions, which are then concentrated and prepared into lithium salts. The adsorption method has a simple process and a high recovery rate. It has greater advantages than other methods from an economic and environmental perspective and is the mainstream development direction in the current market. The key to developing the adsorption method is to make adsorbents with good adsorption selectivity, high recycling rate, relatively low cost, and no pollution to the environment.

[0005] Commonly used adsorbents are titanium adsorbents and aluminum adsorbents. Because aluminum adsorbents have the characteristic of using pure water as an eluent, which forms its advantage of less corrosion to industrial equipment, aluminum adsorbents are the most widely used in the process of extracting lithium from salt lakes. Chinese invention patent application CN116272843A discloses a method for preparing a mesoporous aluminum-based lithium adsorbent, using polyaluminum as an aluminum source, any one or a mixture of lithium chloride, lithium hydroxide, lithium carbonate, and lithium sulfate as a lithium source, and any one of an aqueous solution of sodium carbonate, sodium hydroxide, and potassium hydroxide as an alkali solution. A mesoporous aluminum-based lithium adsorbent precursor is prepared by coprecipitation, and then mixed with a polymer resin for granulation, washing, and drying to finally obtain a mesoporous aluminum-based lithium adsorbent. The mesoporous aluminum-based lithium adsorbent supports the active powder with a mesh polymer skeleton material formed by a polymer resin, and the preparation process is relatively complicated, and its lithium adsorption capacity can only reach 13.5 mg / g at most. Therefore, the preparation process of aluminum-based lithium adsorbents still needs to be simplified, and the lithium adsorption capacity still needs to be further improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an aluminum-based lithium adsorbent with simple process and high lithium adsorption capacity, as well as a preparation method and application thereof.

[0007] In order to achieve the above object, according to the first aspect of the present invention, a method for preparing an aluminum-based lithium adsorbent is provided, and the technical scheme is as follows:

[0008] The preparation method of aluminum-based lithium adsorbent comprises the following steps:

[0009] A composite lithium source solution and a composite aluminum source solution are mixed to form a mixed solution; wherein the composite lithium source comprises a first mixture consisting of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride; the composite aluminum source comprises a second mixture consisting of an acidic aluminum source and an alkaline aluminum source, wherein the acidic aluminum source comprises aluminum chloride and aluminum sulfate, and the alkaline aluminum source comprises sodium metaaluminate;

[0010] Adding alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 4.8 to 6.5 to obtain a solid-liquid mixture; wherein the alkaline solution comprises an aqueous solution of lithium hydroxide;

[0011] The precipitate is collected and dried to obtain the aluminum-based lithium adsorbent.

[0012] Among the above-mentioned composite lithium sources, lithium chloride, lithium nitrate, and lithium acetate have higher solubility in water, which helps to provide a higher concentration of lithium ions in the mixed solution; among them, the aqueous solution of lithium chloride has strong hygroscopicity and electrical conductivity. The hygroscopicity can promote the adsorption of water in the environment and maintain the stability of the solution, while the electrical conductivity helps to enhance the ion conductivity during the reaction; lithium nitrate has strong reactivity and can promote the reaction; lithium acetate can form coordination compounds with other ions or molecules in the solution to help regulate the distribution of lithium ions in the mixed solution, thereby affecting the structure and performance of the final adsorbent. Lithium hydroxide can strongly release OH in water. - Ions have strong reactivity and can promote the precipitation reaction. Lithium carbonate, lithium sulfate, and lithium fluoride have poor solubility in water and can be used as slow-release lithium sources to slowly release lithium ions in the mixed solution, thereby achieving a stable supply of lithium sources and avoiding the problem of reaction instability that may be caused by rapid release.

[0013] Among the above-mentioned composite aluminum sources, aluminum chloride is a strongly acidic salt with strong acidity and hydrophilicity, which can promote the dissolution or reaction of other metal salts. The dissolution rate of aluminum sulfate is slower than that of aluminum chloride, and it can slowly and steadily release aluminum ions with strong hydrophilicity and chemical reactivity, avoiding overreaction or uneven reaction caused by too fast reaction. Sodium aluminate is an alkaline aluminum source with strong alkalinity, which can neutralize the acidity of aluminum chloride and aluminum sulfate and adjust the acidity and alkalinity of the composite aluminum source solution; and the aluminate ions generated by the aluminum ions in sodium aluminate in water can react with other metals or compounds, thereby enriching the aluminum-based structure of the adsorbent.

[0014] It can be seen that the preparation method of the aluminum-based lithium adsorbent of the present invention has the following advantages: (1) The selection of the composite lithium source provides a variety of lithium source forms for the precipitation reaction. These lithium sources have different solubility and reactivity, which can effectively ensure the stable release of lithium and provide flexibility for ion exchange during the reaction process, thereby adjusting the performance of the adsorbent to make it have better selectivity and adsorption capacity. (2) The composite aluminum source combines the advantages of the alkaline aluminum source and the acidic aluminum source and the solubility difference characteristics, cleverly adjusts the acid-base balance and stably releases aluminum ions, provides a stable chemical environment, is conducive to the formation of a stable aluminum-based structure, and thus forms an aluminum-based lithium adsorbent with good adsorption performance. (3) The joint use of the composite lithium source and the composite aluminum source can generate a variety of lithium-aluminum structures, enhancing the selectivity and adsorption capacity of the adsorbent for lithium ions. (4) Lithium hydroxide can be used as a source of alkali solution and can also provide lithium ions, reduce the introduction of impurity metal ions, further enhance the utilization rate of the lithium source, and at the same time affect the formation and distribution of aluminum ions, thereby improving the performance of the adsorbent; in particular, both the alkali solution and the composite lithium source contain lithium hydroxide, and the synergistic effect of the two helps to promote the reaction.

[0015] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: the first mixture is composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride in an equal molar ratio; the second mixture is composed of aluminum chloride, aluminum sulfate, and sodium aluminate in an equal molar ratio. Thus, the setting of the equal molar ratio helps to form a more uniform ion exchange structure during the reaction process, to a certain extent, makes the precipitation reaction between the reactants more uniform, reduces the side reactions that may be caused by excess or deficiency of a certain substance, promotes stable crystal growth, and helps to form an adsorbent with a more compact structure and better surface properties.

[0016] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: the first mixture and / or the second mixture is mixed by ball milling, the ball-to-material mass ratio is (2-6):1, and the ball milling time is 6-24 hours. Thus, the various solid raw materials are broken up into a mixture of smaller particles by ball milling, so that the lithium source and the aluminum source are more evenly and quickly dispersed in the solution, the reaction rate of the lithium source and the aluminum source is increased, and the problem of incomplete reaction or unstable performance caused by uneven distribution is avoided, thereby improving the overall performance of the aluminum-based lithium adsorbent.

[0017] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: the molar amount of the first mixture is 0.06 to 0.25 mol more than the molar amount of the second mixture; thus, a moderate excess of lithium source has the following advantages: (1) ensuring that lithium ions fully participate in the reaction during the reaction, improving the coordination effect between lithium ions and aluminum source, optimizing the surface structure of the aluminum-based lithium adsorbent, and ensuring that the lithium content in the final aluminum-based lithium adsorbent meets the required adsorption performance. (2) adjusting the composition of the adsorbent, effectively promoting the stable embedding and distribution of lithium ions in the final adsorbent, promoting the formation of more abundant adsorption sites, avoiding the relative excess of aluminum source that makes it difficult to form effective lithium adsorption sites and forming an aluminate structure that is not conducive to adsorption. (3) helping to maintain the stable performance of the adsorbent during multiple cycles, so that it maintains a high adsorption capacity when repeatedly used; at the same time, helping the adsorbent to maintain a relatively stable chemical environment during use, thereby improving its long-term stability and durability.

[0018] As a further improvement of the preparation method of the aluminum-based lithium adsorbent, the volumes of the composite lithium source solution and the composite aluminum source solution are equal, and the molar concentration of the second mixture in the mixed solution is 0.06-0.3 mol / L. At this concentration, the reaction between the lithium source and the aluminum source is more stable.

[0019] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: the alkaline solution also includes an organic solvent solution of alkaline lithium-containing organic matter. Therefore, the alkaline lithium-containing organic matter can provide the alkalinity and lithium source required for the precipitation reaction on the one hand, and on the other hand, functional groups can be introduced into the aluminum-based lithium adsorbent, and the introduction of functional groups can enhance the hydrophilicity and / or lithium selectivity, thereby improving the lithium adsorption effect; and the use of organic solvents can improve the solubility of certain lithium sources and aluminum sources in the mixed solution, which is conducive to improving the uniformity and efficiency of the reaction; further, lithium hydroxide and lithium ions in alkaline lithium-containing organic matter have different reactivity, and the use of multiple lithium sources can adjust the solubility and reactivity of the reactants, ensuring that lithium ions can participate in the reaction to the maximum extent during the synthesis process, and improving the selectivity of the reaction and the quality of the adsorbent. Preferably, the alkaline lithium-containing organic matter is at least one of lithium ethyl acetate, lithium acetyl methane, lithium pyrrole, lithium acetonitrile, lithium N-methylimide ethyl acetate, lithium thioacetylacetone, 2-lithium pyridine, 2-lithium oxazole, phenyl lithium, 4-lithium benzoic acid, and 2-lithium pyridine. The alkalinity of these alkaline lithium-containing organic matters is relatively weak, the reaction process will not be too violent, and the reaction is relatively safe.

[0020] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: first add an aqueous solution of lithium hydroxide, and then add an alkaline organic solvent solution of lithium-containing organic matter to the mixed solution. Thus, the aqueous solution of lithium hydroxide added first can quickly increase the alkalinity of the system by providing hydrated ions, so that the crystal nucleus is formed quickly; the organic solvent solution of alkaline lithium-containing organic matter added later can gradually release more lithium ions and further adjust the alkalinity after the system has a certain alkaline environment, so that the crystal nucleus grows stably to form a more regular crystal structure, and improves the adsorption capacity and structural stability of the adsorbent. Preferably, the concentration of lithium hydroxide in the aqueous solution is 0.5-2 mol / L, the dripping speed is 5-20 mL / min, and the pH of the mixed solution is 4.4-5.0; the concentration of alkaline lithium-containing organic matter in the organic solvent solution is 0.2-0.8 mol / L, the dripping speed is 10-25 mL / min, and the pH of the mixed solution is ≤6.5.

[0021] As a further improvement of the preparation method of the above-mentioned aluminum-based lithium adsorbent: it also includes granulating the aluminum-based lithium adsorbent.

[0022] In order to achieve the above object, according to the second aspect of the present invention, an aluminum-based lithium adsorbent is provided, and the technical solution is as follows:

[0023] The aluminum-based lithium adsorbent is prepared by the preparation method described in the first aspect above.

[0024] In order to achieve the above object, according to the third aspect of the present invention, a lithium extraction method is provided, and the technical scheme is as follows:

[0025] The lithium extraction method adopts the aluminum-based lithium adsorbent prepared by the preparation method described in the first aspect to adsorb lithium ions in a lithium-containing solution.

[0026] The present invention is further described below by way of specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through practice of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described clearly and completely below. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention, it should be noted that:

[0028] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.

[0029] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.

[0031] Example 1

[0032] The preparation method of the aluminum-based lithium adsorbent of this embodiment comprises the following steps:

[0033] (1) Mixing equal volumes of a composite lithium source solution and a composite aluminum source solution to form a mixed solution, specifically as follows:

[0034] The composite lithium source is a first mixture composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride in equal molar ratios; 0.18 mol of each of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride is added to 2 L of pure water to obtain the first mixture;

[0035] The composite aluminum source is a second mixture composed of an acidic aluminum source and an alkaline aluminum source, the acidic aluminum source includes aluminum chloride and aluminum sulfate, the alkaline aluminum source includes sodium aluminate, and the second mixture is composed of aluminum chloride, aluminum sulfate, and sodium aluminate in an equal molar ratio; 0.4 mol of each of aluminum chloride, aluminum sulfate, and sodium aluminate is added to 2L of pure water to obtain a second mixture;

[0036] The first mixture and the second mixture are both mixed by ball milling, with a ball-to-material mass ratio of 4:1, and the ball milling time is 12 hours;

[0037] In the mixed solution, the molar amount of the first mixture is 0.06 mol more than the molar amount of the second mixture, and the molar concentration of the second mixture in the mixed solution is 0.3 mol / L.

[0038] (2) adding alkali solution to the mixed solution until the pH value of the mixed solution is 4.8 to obtain a solid-liquid mixture; wherein the alkali solution is an aqueous solution of lithium hydroxide, the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; before adding the alkali solution, stirring for 30 minutes, after the addition of the alkali solution is completed, stirring for 30 minutes, and then standing overnight.

[0039] (3) The precipitate in the solid-liquid mixture is collected and then dried at 75° C. for 3 hours to obtain an aluminum-based lithium adsorbent.

[0040] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 12.4 mg / g.

[0041] Example 2

[0042] The preparation method of the aluminum-based lithium adsorbent of this embodiment comprises the following steps:

[0043] (1) Mixing equal volumes of a composite lithium source solution and a composite aluminum source solution to form a mixed solution, specifically as follows:

[0044] The composite lithium source is a first mixture composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride in equal molar ratios; 0.1 mol of each of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride is added to 2 L of pure water to obtain the first mixture;

[0045] The composite aluminum source is a second mixture composed of an acidic aluminum source and an alkaline aluminum source, the acidic aluminum source includes aluminum chloride and aluminum sulfate, the alkaline aluminum source includes sodium aluminate, and the second mixture is composed of aluminum chloride, aluminum sulfate, and sodium aluminate in an equal molar ratio; 0.2 mol of each of aluminum chloride, aluminum sulfate, and sodium aluminate is added to 2 L of pure water to obtain a second mixture;

[0046] The first mixture and the second mixture are both mixed by ball milling, with a ball-to-material mass ratio of 4:1, and the ball milling time is 12 hours;

[0047] In the mixed solution, the molar amount of the first mixture is 0.1 mol more than the molar amount of the second mixture, and the molar concentration of the second mixture in the mixed solution is 0.15 mol / L.

[0048] (2) adding alkali solution to the mixed solution until the pH value of the mixed solution is 5.3 to obtain a solid-liquid mixture; wherein the alkali solution is an aqueous solution of lithium hydroxide, the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; before adding the alkali solution, stirring for 30 minutes, after the addition of the alkali solution is completed, stirring for 30 minutes, and then standing overnight.

[0049] (3) The precipitate in the solid-liquid mixture is collected and then dried at 75° C. for 3 hours to obtain an aluminum-based lithium adsorbent.

[0050] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 12.8 mg / g.

[0051] Example 3

[0052] The preparation method of the aluminum-based lithium adsorbent of this embodiment comprises the following steps:

[0053] (1) Mixing equal volumes of a composite lithium source solution and a composite aluminum source solution to form a mixed solution, specifically as follows:

[0054] The composite lithium source is a first mixture composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride in equal molar ratios; 0.07 mol of each of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride is added to 2 L of pure water to obtain the first mixture;

[0055] The composite aluminum source is a second mixture composed of an acidic aluminum source and an alkaline aluminum source, the acidic aluminum source includes aluminum chloride and aluminum sulfate, the alkaline aluminum source includes sodium aluminate, and the second mixture is composed of aluminum chloride, aluminum sulfate, and sodium aluminate in an equal molar ratio; 0.08 mol of each of aluminum chloride, aluminum sulfate, and sodium aluminate is added to 2 L of pure water to obtain a second mixture;

[0056] The first mixture and the second mixture are both mixed by ball milling, with a ball-to-material mass ratio of 4:1, and the ball milling time is 12 hours;

[0057] In the mixed solution, the molar amount of the first mixture is 0.25 mol more than the molar amount of the second mixture, and the molar concentration of the second mixture in the mixed solution is 0.06 mol / L.

[0058] (2) adding alkali solution to the mixed solution until the pH value of the mixed solution is 6.5 to obtain a solid-liquid mixture; wherein the alkali solution is an aqueous solution of lithium hydroxide, the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; before adding the alkali solution, stirring for 30 minutes, after the addition of the alkali solution is completed, stirring for 30 minutes, and then standing overnight.

[0059] (3) The precipitate in the solid-liquid mixture is collected and then dried at 75° C. for 3 hours to obtain an aluminum-based lithium adsorbent.

[0060] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 12.7 mg / g.

[0061] Example 4

[0062] Compared with Example 2, the preparation method of the aluminum-based lithium adsorbent of this embodiment is different in that: first, an aqueous solution of lithium hydroxide is added dropwise to the mixed solution until the pH of the mixed solution is 4.4, and then an organic solvent solution containing lithium organic matter is continued to be added dropwise until the pH of the mixed solution is 4.8, thereby obtaining a solid-liquid mixture; wherein the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; the lithium-containing organic matter is lithium ethyl acetate and lithium acetyl methane in an equal molar ratio, with a concentration of 0.8 mol / L, and the dropping speed is 25 mL / min.

[0063] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 13.5 mg / g.

[0064] Example 5

[0065] Compared with Example 4, the preparation method of the aluminum-based lithium adsorbent of this embodiment is different in that: first, an aqueous solution of lithium hydroxide is added dropwise to the mixed solution until the pH of the mixed solution is 4.6, and then an organic solvent solution of lithium-containing organic matter is continued to be added dropwise until the pH of the mixed solution is 5.3, thereby obtaining a solid-liquid mixture; wherein the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; the lithium-containing organic matter is 4-lithium benzoic acid, the concentration is 0.6 mol / L, and the dropping speed is 20 mL / min.

[0066] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 14.2 mg / g.

[0067] Example 6

[0068] Compared with Example 4, the preparation method of the aluminum-based lithium adsorbent of this embodiment is different in that: first, an aqueous solution of lithium hydroxide is added dropwise to the mixed solution until the pH of the mixed solution is 4.8, and then an organic solvent solution of lithium-containing organic matter is continued to be added dropwise until the pH of the mixed solution is 5.3, thereby obtaining a solid-liquid mixture; wherein the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; the lithium-containing organic matter is 2-lithium pyridine, the concentration is 0.4 mol / L, and the dropping speed is 15 mL / min.

[0069] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 14.4 mg / g.

[0070] Example 7

[0071] Compared with Example 4, the preparation method of the aluminum-based lithium adsorbent of this embodiment is different in that: first, an aqueous solution of lithium hydroxide is added dropwise to the mixed solution until the pH of the mixed solution is 5.0, and then an organic solvent solution containing lithium organic matter is continued to be added dropwise until the pH of the mixed solution is 6.5, thereby obtaining a solid-liquid mixture; wherein the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; the lithium-containing organic matter is lithium thioacetylacetone and phenyllithium in an equal molar ratio, with a concentration of 0.2 mol / L, and the dropping speed is 10 mL / min.

[0072] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 13.9 mg / g.

[0073] Comparative Example 1

[0074] Compared with Example 6, the preparation method of the aluminum-based lithium adsorbent of this reference example includes the following steps: 0.2 mol of lithium chloride, 0.1 mol of lithium hydroxide, 0.05 mol of lithium carbonate, 0.1 mol of lithium sulfate, 0.1 mol of lithium nitrate, 0.05 mol of lithium acetate, and 0.1 mol of lithium fluoride are put into 2 L of pure water to obtain a first mixture.

[0075] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 13.3 mg / g.

[0076] Comparative Example 2

[0077] Compared with Example 6, the preparation method of the aluminum-based lithium adsorbent of this comparative example includes the following steps: 0.3 mol of aluminum chloride, 0.2 mol of aluminum sulfate, and 0.1 mol of sodium aluminate are added into 2 L of pure water to obtain a second mixture.

[0078] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 13.1 mg / g.

[0079] Comparative Example 3

[0080] Compared with Example 6, the preparation method of the aluminum-based lithium adsorbent of this reference example includes the following steps: first, an organic solvent solution containing lithium organic matter is added dropwise to the mixed solution until the pH of the mixed solution is 4.8, and then an aqueous solution of lithium hydroxide is added dropwise until the pH of the mixed solution is 5.3, thereby obtaining a solid-liquid mixture; wherein the concentration of lithium hydroxide is 1 mol / L, and the dropping speed is 15 mL / min; the lithium-containing organic matter is 2-lithium pyridine, the concentration is 0.4 mol / L, and the dropping speed is 15 mL / min.

[0081] According to the test, the lithium adsorption capacity of the aluminum-based lithium adsorbent of this embodiment is 13.4 mg / g.

[0082] It can be seen from the above examples that the lithium adsorption capacity of the ungranulated powdered aluminum-based lithium adsorbent prepared in Examples 1-3 can reach more than 12.4 mg / g, and the lithium adsorption capacity of the aluminum-based lithium adsorbent prepared using lithium-containing organic matter as the alkali solution in Examples 4-7 can reach up to 14.4 mg / g. After the recycling test, the lithium adsorption capacity of the 20th use is still as high as 13.5 mg / g, showing excellent adsorption stability. In addition, the present invention does not granulate the aluminum-based lithium adsorbent, so the preparation process is short, which solves the technical problems of complex process and poor adsorption performance of aluminum-based lithium adsorbents in the prior art, and has excellent use prospects.

[0083] Of course, the aluminum-based lithium adsorbent of the present invention can also be used after granulation, that is, another embodiment of the preparation method of the aluminum-based lithium adsorbent of the present invention is to granulate the aluminum-based lithium adsorbent on the basis of the above embodiment, and the granulation method can be but not limited to: 8g of polyethersulfone and 2g of cellulose acetate are added to 100mL of N,N-dimethylformamide, and 40g of powdered aluminum-based lithium adsorbent is added after stirring at 65°C for 2h and continued to stir, and then 2.5mL of polyethylene oxide is added and continued to stir for 3h to form a uniform slurry, and a syringe pump is used to slowly drop it into water to form particles, and then washed with water and dried at 60°C to obtain a granular aluminum-based lithium adsorbent. After testing, the lithium adsorption capacity of the aluminum-based lithium adsorbent particles obtained by further granulating the aluminum-based lithium adsorbent of Example 6 is 15.0mg / g.

[0084] The aluminum-based lithium adsorbent of the present invention is prepared by the preparation method described in any one of the above embodiments.

[0085] The embodiment of the lithium extraction method of the present invention is to use the aluminum-based lithium adsorbent prepared by the preparation method described in any of the above embodiments to adsorb lithium ions in a lithium-containing solution. The lithium-containing solution can be, but is not limited to, salt lake brine in a salt lake lithium extraction process.

[0086] The above-mentioned lithium adsorption capacity test method is as follows: 1g of aluminum-based lithium adsorbent is dried to constant weight and then added to 0.1L of Uyuni Salt Lake brine (lithium concentration is 601mg / L); then, the mixed solution is placed in a constant temperature water bath oscillator for 1h to adsorb lithium; then, the aluminum-based lithium adsorbent is separated by filtration; then, the aluminum-based lithium adsorbent is added to 100mL of pure water and shaken in a constant temperature water bath for 1h, and then washed and analyzed. Lithium adsorption capacity Q e The calculation formula for (mg / g) is: Wherein, C0 is the concentration of lithium ions in the desorption solution (mg / L), V is the volume of the adsorption solution (i.e., Uyuni Salt Lake brine) (L), and m is the mass of the aluminum-based lithium adsorbent (g).

[0087] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum-based lithium adsorbent, characterized in that: The following steps are involved: A composite lithium source solution and a composite aluminum source solution are mixed to form a mixed solution; wherein the composite lithium source comprises a first mixture consisting of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate, and lithium fluoride; the composite aluminum source comprises a second mixture consisting of an acidic aluminum source and an alkaline aluminum source, wherein the acidic aluminum source comprises aluminum chloride and aluminum sulfate, and the alkaline aluminum source comprises sodium metaaluminate; Adding alkaline solution dropwise to the mixed solution until the pH value of the mixed solution is 4.8 to 6.5 to obtain a solid-liquid mixture; wherein the alkaline solution comprises an aqueous solution of lithium hydroxide; The precipitate is collected and dried to obtain the aluminum-based lithium adsorbent.

2. The method for preparing the aluminum-based lithium adsorbent according to claim 1, characterized in that: The first mixture is composed of lithium chloride, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, lithium acetate and lithium fluoride in an equal molar ratio; the second mixture is composed of aluminum chloride, aluminum sulfate and sodium aluminate in an equal molar ratio.

3. The method for preparing the aluminum-based lithium adsorbent according to claim 2, characterized in that: The first mixture and / or the second mixture is mixed by ball milling, the ball-to-material mass ratio is (2-6):1, and the ball milling time is 6-24 hours.

4. The method for preparing the aluminum-based lithium adsorbent according to claim 1, characterized in that: The molar amount of the first mixture is 0.06-0.25 mol more than the molar amount of the second mixture; the volumes of the composite lithium source solution and the composite aluminum source solution are equal; and the molar concentration of the second mixture in the mixed solution is 0.06-0.3 mol / L.

5. The method for preparing the aluminum-based lithium adsorbent according to claim 1, characterized in that: The alkaline solution also includes an alkaline organic solvent solution containing lithium organic matter.

6. The method for preparing the aluminum-based lithium adsorbent according to claim 5, characterized in that: The alkaline lithium-containing organic matter is at least one of lithium ethyl acetate, lithium acetyl methane, lithium pyrrole, lithium acetonitrile, lithium N-methyliminoethyl acetate, lithium thioacetylacetone, 2-lithium pyridine, 2-lithium oxazole, phenyl lithium, 4-lithium benzoic acid, and 2-lithium pyridine; First, add an aqueous solution of lithium hydroxide and then add an organic solvent solution of an alkaline lithium-containing organic substance into the mixed solution.

7. The method for preparing the aluminum-based lithium adsorbent according to claim 6, characterized in that: The concentration of lithium hydroxide in the aqueous solution is 0.5-2 mol / L, the dropping speed is 5-20 mL / min, and the pH value of the mixed solution is 4.4-5.0; the concentration of alkaline lithium-containing organic matter in the organic solvent solution is 0.2-0.8 mol / L, the dropping speed is 10-25 mL / min, and the mixed solution is added until the pH value is ≤6.

5.

8. The method for preparing the aluminum-based lithium adsorbent according to claim 1, characterized in that: The method also includes granulating the aluminum-based lithium adsorbent.

9. Aluminum-based lithium adsorbent, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium extraction method, characterized in that: The aluminum-based lithium adsorbent prepared by the preparation method described in any one of claims 1 to 8 adsorbs lithium ions in a lithium-containing solution.

Citation Information

Patent Citations

  • Mesoporous aluminum-based lithium adsorbent as well as preparation method and application thereof

    CN116272843A